Stage IV EGFR Mutation-Negative and ALK Mutation-Negative Lung Adenocarcinoma: Long-Term Survival is Possible - Kedia, Shiksha (Cureus, 2015)
Lung cancer is the leading cause of cancer death in the United States with a five-year survival of 16.8% for all stages and median survival of four months for Stage IV disease. We report a case of a 54-year-old male with a seven-year survival after being diagnosed with Stage IV epidermal growth factor receptor (EGFR) mutation-negative and anaplastic lymphoma kinase (ALK) mutation-negative adenocarcinoma of the lung, demonstrating an exceptional response to treatment.